Answer:
7/10
Step-by-step explanation:
Out of the ten spins seven landed on blue.
I hope this helps :)
You flip the signs when you are dividing by a negative value.
-2x+3>15
-2x>15-3
-2x>12
x<12/-2
x<-6
Now to test this
Try putting x in the original equation when it is -5.
-2(-5)+3>15
10+3>15
13>15
This is false because our answer says x is less than -6.
Now any value less than -6 will work so let's go with -7.
-2(-7)+3>15
14+3>15
17>15
This result is True.
Hope this helps out!
Answer:
A, C and F
Step-by-step explanation:
The given function is
It is an exponential function of the form
On comparing both the functions, we get
It means the initial value is 5 and growth factor is 3.
Since both values are positive it means the given functions is an exponential growth function, therefore,
1. The graph is increasing by a common ratio of 3.
2. As x increases, y increases.
3. As x decreases, y approaches 0.
Hence, the correct options are A, C and F.
Answer:
In the equation, it divides 21 by x before knowing what x is, and gets it incorrect. Instead, you need to divide 21 by -4.2.
Step-by-step explanation:
-4.2x = 21
-------------
-4.2
x = -5
Answer:
What is the point used in the equation of the line y+4=1/2(x-2)
The other format for straight-line equations is called the "point-slope" form. For this one, they give you a point (x1, y1) and a slope m, and have you plug it into this formula:
y - y1 = m(x - x1)
Don't let the subscripts scare you. They are just intended to indicate the point they give you. You have the generic "x" and generic "y" that are always in your equation, and then you have the specific x and y from the point they gave you; the specific x and y are what is subscripted in the formula. Here's how you use the point-slope formula
They've given me m = 4, x1 = -1, and y1 = -6. I'll plug these values into the point-slope form, and solve for "y=":
y - y1 = m(x - x1)
y - (-6) = (4)(x - (-1))
y + 6 = 4(x + 1)
y + 6 = 4x + 4
y = 4x + 4 - 6
y = 4x - 2